Enhancing Student Engagement and Academic Performance Through Digital Literacy : A Transformative Approach in Canva Application - Novita Sari Hutapea; Zefanya Putra Julu Manullang; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study investigates the impact of Canva, a digital literacy tool, on enhancing student engagement and academic performance through the lens of Self-Determination Theory by Johnmarshall Reeve (2012). Using qualitative methods, data were collected from student responses via questionnaires. The findings reveal that Canva positively influences the four dimensions of engagement: behavioral, emotional, cognitive, and agentic. Behavioral engagement is supported through its intuitive tools that promote focus and persistence. Emotional engagement is enhanced by evoking positive emotions and reducing stress. Cognitive engagement is fostered by encouraging critical thinking and creativity, while agentic engagement empowers students to take ownership of their learning processes. Despite challenges such as limited free features, students effectively utilized Canva’s resources to overcome these barriers. The study concludes that Canva offers a transformative approach to education, promoting 21st-century skills and bridging traditional learning with digital literacy. Future improvements could expand free templates, collaborative features, and educational resources, further amplifying its benefits in academic settings.